Hsp90 inhibition decreases mitochondrial protein turnover. - Daciana H Margineantu; Christine B Emerson; Dolores Diaz; David M Hockenbery (PLoS ONE)
Background Cells treated with hsp90 inhibitors exhibit pleiotropic changes, including an expansion of the mitochondrial compartment, accompanied by mitochondrial fragmentation and condensed mitochondrial morphology, with ultimate compromise of mitochondrial integrity and apoptosis. Findings We identified several mitochondrial oxidative phosphorylation complex subunits, including several encoded by mtDNA, that are upregulated by hsp90 inhibitors, without corresponding changes in mRNA abundance. Post-transcriptional accumulation of mitochondrial proteins observed with hsp90 inhibitors is also seen in cells treated with proteasome inhibitors. Detailed studies of the OSCP subunit of mitochondrial F1F0-ATPase revealed the presence of mono- and polyubiquitinated OSCP in mitochondrial fractions. We demonstrate that processed OSCP undergoes retrotranslocation to a trypsin-sensitive form associated with the outer mitochondrial membrane. Inhibition of proteasome or hsp90 function results in accumulation of both correctly targeted and retrotranslocated mitochondrial OSCP. Conclusions Cytosolic turnover of mitochondrial proteins demonstrates a novel connection between mitochondrial and cytosolic compartments through the ubiquitin-proteasome system. Analogous to defective protein folding in the endoplasmic reticulum, a mitochondrial unfolded protein response may play a role in the apoptotic effects of hsp90 and proteasome inhibitors.